2016
DOI: 10.1016/j.polymer.2016.07.047
|View full text |Cite
|
Sign up to set email alerts
|

Unswollen layer of cross-linked polyisoprene at the solid interface

Abstract: The density profile in a thin cross-linked polyisoprene (PI) film spin-coated on a quartz substrate in n-hexane was examined by specular neutron reflectivity. We found two layers with different PI densities at the substrate interface. The characteristics of the layers are discussed in terms of bound rubber typically associated with the field of rubber materials and adsorbed layers typically associated with the field of glassy materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 63 publications
1
32
0
Order By: Relevance
“…Similar observations have been found in other work using neutron scattering and echo techniques. Shimomura et al 43 have identified that a tightly bound layer (about 5 nm) found in cross-linked polyisoprene on silica showed little or no penetration of deuterated n-hexane, a good solvent for polyisoprene. In the case of polybutadiene on carbon black, Jiang et al 42 found that a 0.5 nm layer of "inner" polymer was found to be near the particle surface and unswollen with deuterated toluene.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Similar observations have been found in other work using neutron scattering and echo techniques. Shimomura et al 43 have identified that a tightly bound layer (about 5 nm) found in cross-linked polyisoprene on silica showed little or no penetration of deuterated n-hexane, a good solvent for polyisoprene. In the case of polybutadiene on carbon black, Jiang et al 42 found that a 0.5 nm layer of "inner" polymer was found to be near the particle surface and unswollen with deuterated toluene.…”
Section: ■ Discussionmentioning
confidence: 99%
“…By dispersing a small amount of fillers, such as carbon black and fibers, glass fibers, silica nanoparticles, talc, and so on, into a polymer matrix, multiple macroscopic properties of the polymer can be substantially improved. Polymer chains adsorbed onto the filler, which generally exhibit different aggregation states and relaxation dynamics from those in the bulk, are believed to play crucial roles in the improvement of mechanical properties of polymer nanocomposites. Such can be seen in the bulk glass transition temperature ( T g b ), elastic modulus, and rheological responses for polymer nanocomposites with respect to the bulk properties. Over the past few decades, many efforts have been devoted to gaining a better understanding of the structural and dynamic properties of adsorbed polymer chains within the interfacial layer. ,,, …”
mentioning
confidence: 99%
“…Meanwhile, many studies have suggested that the adsorption and relaxation processes of chains at the solid interface are much more complicated than previously thought. ,, The relaxation dynamics can be faster for weakly, or loosely, adsorbed chains than for ones in direct contact with the solid surface. ,, This means that different techniques with various depths and time scale resolutions might detect the relaxation dynamics of different portions of adsorbed chains, revealing dynamic behaviors of adsorbed chains in more detail. Such techniques will lead to a better understanding of polymer behavior at interfaces.…”
mentioning
confidence: 99%
“…In the field of composite materials composed of rubber polymers, the “bound rubber” concept, where an immobilized and insoluble polymer layer exists at the surface of inorganic fillers and plays an important role in the mechanical properties, has been widely accepted. , The interfacial layer is believed to consist of two types of chains with different conformations: “tightly” and “loosely” adsorbed chains. , Tightly adsorbed chains are in direct contact with the solid surface and possess many adsorption points. In addition, there are chains that are partially adsorbed on the solid surface and connected to chains in the bulk phase.…”
mentioning
confidence: 99%